STATISTICAL SAMPLING AND THE ACCOUNTING CURRICULUM. - Backer, Morton; Fertig, Paul E. (The Accounting Review, 1958)
Abstract Recent development which promises to have considerable effect on future accounting practice is the application of statistical sampling techniques to accounting. Sufficient experimentation has already taken place in both public and private accounting to indicate that sampling will shortly become an indispensable accounting tool. This raises challenging problems to accounting educators that can hardly be ignored any longer. The authors, in this article, are directing questions on the best way of teaching advanced sampling method to the accounting students and in developing competence in this area. The American Institute of Certified Public Accountants has recognized its increasing importance to auditors by establishing a committee to deal with the problem. The Institute of Internal Auditors has created a similar committee. Statistical sampling not only can produce equivalent or greater accuracy than a complete investigation, but it can also accomplish this in less time and at less cost.